Cryptosporidium species and subtypes in animals inhabiting drinking water catchments in three states across Australia. (1st May 2018) - Zahedi, Alireza; Monis, Paul; Gofton, Alexander W.; Oskam, Charlotte L.; Ball, Andrew; Bath, Andrew; Bartkow, Michael; Robertson, Ian; Ryan, Una
Abstract: As part of long-term monitoring of Cryptosporidium in water catchments serving Western Australia, New South Wales (Sydney) and Queensland, Australia, we characterised Cryptosporidium in a total of 5774 faecal samples from 17 known host species and 7 unknown bird samples, in 11 water catchment areas over a period of 30 months (July 2013 to December 2015). All samples were initially screened for Cryptosporidium spp. at the 18S rRNA locus using a quantitative PCR (qPCR). Positives samples were then typed by sequence analysis of an 825 bp fragment of the 18S gene and subtyped at the glycoprotein 60 ( gp60 ) locus (832 bp). The overall prevalence of Cryptosporidium across the various hosts sampled was 18.3% (1054/5774; 95% CI, 17.3–19.3). Of these, 873 samples produced clean Sanger sequencing chromatograms, and the remaining 181 samples, which initially produced chromatograms suggesting the presence of multiple different sequences, were re-analysed by Next- Generation Sequencing (NGS) to resolve the presence of Cryptosporidium and the species composition of potential mixed infections. The overall prevalence of confirmed mixed infection was 1.7% (98/5774), and in the remaining 83 samples, NGS only detected one species of Cryptosporidium . Of the 17 Cryptosporidium species and four genotypes detected (Sanger sequencing combined with NGS), 13 are capable of infecting humans; C. parvum, C. hominis, C. ubiquitum, C. cuniculus, C. meleagridis, C. canis, C. felis, C. muris, C. suis, C. scrofarum, C. bovis, C. erinacei and C. fayeri. Oocyst numbers per gram of faeces (g −1 ) were also determined using qPCR, with medians varying from 6021–61, 064 across the three states. The significant findings were the detection of C. hominis in cattle and kangaroo faeces and the high prevalence of C. parvum in cattle. In addition, two novel C. fayeri subtypes (IVaA11G3T1 and IVgA10G1T1R1) and one novel C. meleagridis subtype (IIIeA18G2R1) were identified. This is also the first report of C. erinacei in Australia. Future work to monitor the prevalence of Cryptosporidium species and subtypes in animals in these catchments is warranted. Graphical abstract: Image 1 Highlights: First study to apply NGS on a large-scale to detect mixed Cryptosporidium infections in animals. Identification of C. hominis and C. parvum in kangaroo and cattle faecal samples. Identification of two novel C. fayeri subtypes in kangaroos. Identification of one novel C. meleagridis subtype in birds. Implications of zoonotic Cryptosporidium spp. for management of drinking water sources.